Novel aziridine esters by the addition of aromatic nitrogen heterocycles to a 2H-azirine-3-carboxylic ester - Alves, Maria José Chão (2000)
Methyl 2-(2,6-dichlorophenyl)-2H-azirine-3-carboxoylate acts as an efficient alkylating agent for a variety of five-membered aromatic heterocycles. The aziridines derived from heterocycles that bear an alpha-carbonyl substituent react with TFA to give pyrroloimidazoles; 2,6-dichlorobenzaldehyde is also produced.